Abnormal Psychology - Edited by Oltmanns, Thomas F. and Emery, Robert E. (India Pearson, 2016)
Fully updated for DSM-5, this exciting revision complements the abnormal psychology course by providing 17 case histories based on the authors' clinical experiences. The casebook also provides three "You Decide" cases - written without diagnosis or treatment, so students can identify disorders and suggest appropriate therapies.
Include Index, References and Illustration
Keywords: Psychology, Pathological -- Psychiatry